Embracing Implementation Science in Nursing and Midwifery to Translate Evidence-based Interventions into Policies and Clinical Practice. - Setswe, Geoffrey; Zungu, Lindiwe (Africa Journal of Nursing & Midwifery, 2022)
Evidence-based interventions (EBIs) are the subject of dissemination and implementation efforts in nursing and midwifery. Nursing and midwifery research generates mountains of EBIs with proven efficacy and effectiveness. These include interventions such as the diabetes prevention programme, practices such as cervical cancer screening, and workplace policies such as Covid-19 vaccination. However, evidence is not always used in practice, and there are many examples of problematic implementation of research into practice. Implementation science, defined as "the scientific study of methods to promote the systematic uptake of research findings and other evidence-based practice into routine practice ... to improve the quality and effectiveness of health services" (Eccles and Mittman 2006), is increasingly being used to implement evidence-based nursing interventions in real-life settings.